2020
DOI: 10.1002/hon.2742
|View full text |Cite
|
Sign up to set email alerts
|

Long‐lasting efficacy and safety of lenalidomide maintenance in patients with relapsed diffuse large B‐cell lymphoma who are not eligible for or failed autologous transplantation

Abstract: We report final results of a phase II trial addressing efficacy and feasibility of lenalidomide maintenance in patients with chemosensitive relapse of diffuse large B-cell lymphoma (DLBCL) not eligible for or failed after autologous stem cell transplantation (ASCT). Patients with relapsed DLBCL who achieved at least a partial response to salvage chemoimmunotherapy were enrolled and treated with lenalidomide 25 mg/day for 21 of 28 days for 2 years or until progression or unacceptable toxicity. Primary endpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Wang M et al [ 41 ] reported common grades 3–4 hematological adverse events (≥ 10 events), including neutropenia (53%), lymphopenia (40%), thrombocytopenia (33%), leukopenia (27%) and anemia (18%). Ferreri et al [ 42 ] found lenalidomide was well tolerated, especially in this elderly population, with the exception of neutropenia, grade-4 toxicities occurred in < 1% of courses. Our study summarized grade ≥ 3 hematological toxicity events.…”
Section: Discussionmentioning
confidence: 99%
“…Wang M et al [ 41 ] reported common grades 3–4 hematological adverse events (≥ 10 events), including neutropenia (53%), lymphopenia (40%), thrombocytopenia (33%), leukopenia (27%) and anemia (18%). Ferreri et al [ 42 ] found lenalidomide was well tolerated, especially in this elderly population, with the exception of neutropenia, grade-4 toxicities occurred in < 1% of courses. Our study summarized grade ≥ 3 hematological toxicity events.…”
Section: Discussionmentioning
confidence: 99%
“…Our initial screening led to the identification of 1237 potentially eligible studies (1231 from PubMed, EMBASE, and Cochrane Library, and 6 from other sources). We ultimately excluded 1226 of these studies based on the inclusion and exclusion criteria, and included 11 publications from 10 studies from that were published from 2008 to 2020 (Figure 1 and Table 1) (7,8,(14)(15)(16)(17)(18)(19)(20)(21)(22). Five of these studies were prospective one-arm studies (7,8,15,16,20,21), four were retrospective analyses (14,17,18,22), and one was a randomized controlled trial (19).…”
Section: Basic Characteristics Of Studiesmentioning
confidence: 99%
“…We ultimately excluded 1226 of these studies based on the inclusion and exclusion criteria, and included 11 publications from 10 studies from that were published from 2008 to 2020 (Figure 1 and Table 1) (7,8,(14)(15)(16)(17)(18)(19)(20)(21)(22). Five of these studies were prospective one-arm studies (7,8,15,16,20,21), four were retrospective analyses (14,17,18,22), and one was a randomized controlled trial (19). The sample size ranged from 15 to 153 patients, and the median patient age ranged from 51 to 79 years old.…”
Section: Basic Characteristics Of Studiesmentioning
confidence: 99%
“…Lenalidomide is a well-known drug that blocks the BCR-NF-κB pathway by targeting the E3 ubiquitin ligase component cereblon, with antineoplastic consequences [170]. The efficacy of lenalidomide maintenance has yielded positive results in DLBCL patients after salvage or frontline therapy [171]. DLBCL demonstrated a substantial activity in patients with R/R, especially in the non-GBC and ABC-DLBCL subtypes.…”
Section: Nf-κb Inhibitionmentioning
confidence: 99%